Comparative study of Watson's and Cairns's trabeculectomies in a Black population with open angle glaucoma. Issue 2 (February 1977) - David, R; Freedman, J; Luntz, M H
Abstract : A comparative study of the effectiveness of Watson's and Cairns's trabeculectomy in a Black South African population with open-angle glaucoma is presented. The eventual success rate of 91-6% is comparable with that found in Whites, and the results were similar with both methods.